Pergeseran Bentuk dan Makna dalam Penerjemahan Antologi Puisi Sundel Bolong Njero Senthong - PRESSANTI, DESI ARI (Kementerian Sekretariat Negara Republik Indonesia, 2019)
Translation is generally understood as an attempt to transfer messages or meaning of the text (in this case poetry) across from the Source Language to the Target Language, so readers who do not speak of the Source Language can understand the messages conveyed by the author. Translating poetry is relatively more difficult compared to translating other literary works since the translators are expected to be able to transfer the message as well as to maintain it’s aesthetic value. The aesthetic value of the poetry from the Source Language is part of the constructive elements which harmoniously form a beautiful poetry. In this regards, a good translator has to deliver a corresponding message and at the same time keep the aesthetic senses of the poetry for the readers. The attempt to maintain the aesthetic elements of the poetry often results in shifts in form and meaning of the poetry. The object of this research is the Anthology of Poetry of Sundel Bolong Njero Sentong by Rini Tri Puspohardini translated from Javanese to Indonesian language by Sosiawan Leak. The objective of the study is to describe the shifts in form and meaning occurred as the result of the translation of this anthology. The method used in this research is the descriptive qualitative method. Keywords: poetry, translation, form shift, meaning shift.